2019
DOI: 10.1016/j.talanta.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Realistic measurement uncertainties for marine macronutrient measurements conducted using gas segmented flow and Lab-on-Chip techniques

Abstract: Accurate and precise measurements of marine macronutrient concentrations are fundamental to our understanding of biogeochemical cycles in the ocean. Quantifying the measurement uncertainty associated with macronutrient measurements remains a challenge. Large systematic biases (up to 10%) have been identified between datasets, restricting the ability of marine biogeochemists to distinguish between the effects of environmental processes and analytical uncertainty. In this study we combine the routine analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
(76 reference statements)
1
15
0
Order By: Relevance
“…Seawater samples were analysed using a gas segmented flow manifold, Seal AA3 (Norderstedt, Germany), combined with a standard spectrophotometric technique (molybdenum blue) (Hydes et al, 2010). The chemistry is almost identical to that used in the LoC analyser, and previous studies have demonstrated that data generated via gas segmented flow analysis is directly comparable to that generated via LoC analysers (Clinton-Bailey et al, 2017;Grand et al, 2017;Birchill et al, 2019a). The limit of detection for gas segmented flow analysis is 0.01 µM in seawater (SEAL-Analytical, 2019).…”
Section: Lab-on-chip Data Screening and Comparison With Nearby Ship-based Measurements And Climatological Datamentioning
confidence: 87%
See 2 more Smart Citations
“…Seawater samples were analysed using a gas segmented flow manifold, Seal AA3 (Norderstedt, Germany), combined with a standard spectrophotometric technique (molybdenum blue) (Hydes et al, 2010). The chemistry is almost identical to that used in the LoC analyser, and previous studies have demonstrated that data generated via gas segmented flow analysis is directly comparable to that generated via LoC analysers (Clinton-Bailey et al, 2017;Grand et al, 2017;Birchill et al, 2019a). The limit of detection for gas segmented flow analysis is 0.01 µM in seawater (SEAL-Analytical, 2019).…”
Section: Lab-on-chip Data Screening and Comparison With Nearby Ship-based Measurements And Climatological Datamentioning
confidence: 87%
“…The oceanographic research community is experiencing a dramatic increase in capability as autonomous technologies Grand et al, 2017). Error bars are laboratory estimates of combined (random + systematic) relative uncertainty (Birchill et al, 2019a). (B) Statistically significant inverse linear correlation between temperature and PO 4 3− concentration from dives 691, 692, and 693…”
Section: Assessing the Extent To Which This Research Has Expanded Glider Sensor Capabilities For Oceanographic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the quality control of field measurements will become as stringent as those for laboratory analysis and this for all the analytical approaches. One approach to determine uncertainty of nutrient measurements from LoC sensors is also presented by Birchill et al (2019). Quality control charts for the analysis of QC samples used by wet chemical analyzers should be recorded and checked to make sure that the analytical performance is continuously maintained and in accordance with the requirements.…”
Section: Consideration Of Methods Performance Assessment For In Situ mentioning
confidence: 99%
“…Over the last decade, another important milestone in the quality control of nutrient measurements has been the development and application of CRMs for nutrients. A range of CRMs are now available, which, when used and applied correctly, are starting to improve the quality of nutrient analysis in laboratories and allows for the determination of analytical measurement uncertainty (Aoyama et al, 2018;Birchill et al, 2019).…”
Section: Laboratory Benchmark Techniques For Nutrient Analysis In Seamentioning
confidence: 99%